2016
DOI: 10.2319/022416-159.1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone metabolism during early orthodontic tooth movement with aligners

Abstract: Objective: To evaluate the expression of receptor activator of nuclear factor-kappa ligand (RANKL), osteoprotegerin (OPG), osteopontin (OPN), interleukin 1b (IL-1b), and transforming growth factor ß1 (TGF-ß1) in the gingival crevicular fluid (GCF) of teeth subjected to orthodontic forces released by aligners. Materials and Methods: A total of 10 healthy, adult patients were selected to participate in this split-mouth study. The treatment plan was designed to obtain only one movement with the first aligner: dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
4
23
0
1
Order By: Relevance
“…In contrast, IL-1β expression levels showed fluctuations over time, which is consistent with the findings by Iwasaki et al, 18 where a peak concentration of this cytokine was not characterized within the first 24 h. Castrofolio et al 19 demonstrated that a peak concentration of IL-1β occurred 21 d after orthodontic activation with Invisalign.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, IL-1β expression levels showed fluctuations over time, which is consistent with the findings by Iwasaki et al, 18 where a peak concentration of this cytokine was not characterized within the first 24 h. Castrofolio et al 19 demonstrated that a peak concentration of IL-1β occurred 21 d after orthodontic activation with Invisalign.…”
Section: Discussionsupporting
confidence: 87%
“…However, this study analyzed a total of 180 sites and a large number of previous studies used similar sample sizes. 1 , 12 - 17 , 19 - 20 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The result closely matches that obtained by other authors, where a posttreatment IL-1β concentration increase was reported [10]. In the study carried out by Italian researchers, IL-1β concentration in the area of applied force shows an increase during tooth movement [19]. Some researchers showed that levels of IL-1β increased in the root resorption area in tooth movements of treated rats [20] IL-1β is a strong cytokine of the periodontal environment in the course of tooth movement [21].…”
Section: Discussionsupporting
confidence: 92%
“…Since OPN is ubiquitously expressed in periodontal remodeling during orthodontic tooth movement, various research groups have implicated OPN as a biomarker to assess the tissue response with respect to orthodontic treatment [ 61 ]. The samples were collected from GCF and a protein levels were assessed [ 61 65 ]. DNA methylation biomarkers of Spp1 gene and other osteogenic genes may also be helpful to understand the individual variability in response to orthodontic treatment [ 66 ].…”
Section: Future Directionsmentioning
confidence: 99%